COVID-19: An Organizational-theory-guided Holistic Self-caring and Resilience Project. (December 2021) - Barnett, Paras; Barnett, Michael; Borgueta, Elizabeth; Moreno, Janette V.; Watson, Jean
Purpose: In response to the coronavirus disease 2019 (COVID-19) global human caring crisis, this article describes an innovative, theory-guided, holistic practice project at a major academic medical center in Northern California. The purpose of this theory-guided COVID-19 project was to address the self-care needs of caregivers so they could better care for patients/families who are confronting daily pandemic demands.Study design: The organization's professional practices are guided by Watson's theory of human caring and Caritas Processes. This setting has 16 Caritas Coaches® who have acquired expertise in human caring from an accredited program of the Watson Caring Science Institute (www.watsoncaringscience.org ).Methods: Caritas Coaches® were mobilized to implement holistic caring–healing modalities such as aromatherapy and mindfulness meditation throughout the organization.Findings: By addressing the self-care needs of caregivers, the organizational culture shifted from fear, fatigue, stress, and burnout, to more intentional conscious, mindful, caring presence, gratitude, and purpose.Conclusion: This study has implications for other institutions regarding theory-guided practice and system responses to self-care needs of staff. This study provides an overview of the project from its origin to implementation and outcomes.